PERLINDUNGAN HUKUM BAGI PENGGUNA JASA EYELASH EXTENSION DAN SULAM ALIS PADA SALON KECANTIKAN DI KOTA SAMARINDA BERDASARKAN UNDANG UNDANG NO 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Merda Angela (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTLegal protection for users of Eyelash Extension and Eyebrow Embroidery services at beauty salon services in the city of Samarinda based on Law No. 8 of 1999 concerning Consumer Protection, there are formulations of research problems, namely 1) How is the practice of eyelash extension and eyebrow embroidery services at beauty salons in Samarinda city; 2) What is the form of legal protection for users of eyelash extension and eyebrow embroidery services at a beauty salon in Samarinda city.The research method used by researchers is a type of normative research. The data collection technique used in this study was literature study and was supported by interviews in the form of several oral questions. Meanwhile, data analysis using primary, secondary, and non-legal materials has been processed deductively.As for the results of the study, it can be concluded that 1) In the practice of the eyelash extension installation service, the process of connecting artificial eyelashes to the original eyelashes, the process of connecting this eyelash also lasts for 30 minutes to 1 hour and the eyebrow embroidery service, the eyebrow embroidery technician will clean the hair- fine hair on the eyebrows to map the shape of the eyebrows that match the service user's face. this eyebrow embroidery procedure ranges from 1-2 hours; 2) Review of Law Number 8 of 1999 concerning Consumer Protection, namely in Article 4 of Law Number 8 of 1999 it has been mentioned regarding consumer rights, and in article 7 of Law Number 8 of 1999 concerning Consumer Protection it is also stated that every business actors have the obligation to provide compensation, compensation and / or compensation for losses resulting from the use of goods and / or services. This is also regulated in the provisions of Article 26 of Law No. 8 of 1999 concerning Consumer Protection, which states that if consumers suffer losses in the form of damage, pollution, or financial and health losses due to consuming traded products, the producers as business actors are obliged to provide compensation. , whether in the form of refunds, replacement of goods, maintenance, or by providing compensation.Keywords : Consumer Protection, Service Practices, Eyelash Extension and Embroidery Eyebrows, Compensation